Comparative performance analysis of Bipolar and Unipolar pseudo-based inverter for off-grid photovoltaic application - Razi, Atikah; Ab Syukor, Syahar Azalia; Hidayat, M.Nabil (UiTM Press, 2021)
In this paper, a comparative performance analysis of two-switch Pseudo-inverter and Full-bridge inverter for Off-Grid Photovoltaic (OGPV) system is presented using single 250W-PV module. The performance of Pseudo-inverter and conventional Full-bridge inverter in terms of total harmonic distortion of the output voltage and current are compared based on the internal control of the inverter (open loop control) using Bipolar and Unipolar Sinusoidal Pulse-Width Modulation (SPWM). The total harmonic distortion (THD) of the conventional Full-bridge inverter and Pseudo-inverter, before and after implementation of filtering components also being analyzed. The results show that the Unipolar Pseudo-inverter with filter significantly provide lowest THD which are (5.01% and 5.35%) compared to conventional Unipolar Full-bridge inverter (13.9% and 35.55%), for current harmonic and voltage harmonic, THDi and THDv respectively. All the analytical work was performed using MATLAB Simulink software.